Rethinking history and epistemology in mathematics education*. Issue 6 (17th August 2020) - Furinghetti, Fulvia
Abstract : For a long time, mathematics educators have shown interest in the use of history of mathematics in mathematics teaching. This article discusses some interesting reasons put forwards by the supporters of this use and their epistemological assumptions. The initial part of the article provides a short account of the setting in which the first discussions and the first experiments concerning the use of history in mathematics teaching took place. Afterwards, the article outlines the development of the community of scholars interested in the relationship between history and pedagogy of mathematics, which in 1976 was officially established as the group HPM (History and Pedagogy of Mathematics) affiliated to ICMI (International Commission on Mathematical Instruction). The materials produced in this context constitute a background and a source for researchers and for mathematics teachers wishing to explore the opportunity offered by history in their teaching. About the introduction of history of mathematics in the classroom, the article focuses on two main streams of action: – history for promoting the image of mathematics as a vivid discipline with links with reality and culture, – history for dealing with mathematical concepts. An efficient introduction of history in teaching entails adequate teachers' historical knowledge. Then a part of this article is dedicated to discuss the role of this knowledge and to present how history may be used in teacher training programs. At the end of the article, some frequent objections put forwards by teachers about the possibility of introducing history in their teaching are presented. The conclusion is that, though there are difficulties and some contexts are not favourable to this introduction, in suitable contexts, the effort required for facing this endeavour will be rewarded by significant improvements in the classroom life.